Migration as a Source of Suffering in the Context of the Biographical Experience of the Process of Transformation in Poland. Case Study of Weronika’s Life History - Wygnańska, Joanna (Qualitative Sociology Review, 2019)
The article focuses on the case study of the life history of Weronika, a person biographically experiencing the consequences of the transformation process in Poland. On the one hand, the text concentrates on showing the change in the status of the narrator’s family from a privileged position in the socialist period to the experience of unemployment and poverty after 1989. On the other hand, the text analyzes the necessity of the narrator’s mother’s emigration to Italy in the mid-1990s. Thus, the article focuses on the narrator’s experience in the context of being a migrant woman’s child. This experience is related to the time of socialization and education, which was difficult for the narrator, and the consequence of which is shown in the text in connection to the narrator’s persistence in trajectory. The text also presents the perspective of transnational motherhood within the framework of Polish women’s migrations after 1989. Also, an important perspective adapted in the article is the experience of migration by the narrator, who at the time of the interview has also been living in Italy for 10 years. Permanent emigration of the narrator is associated in her life history with high biographical costs. The article is, therefore, an attempt to present migration as a source of suffering in relation to the context of being a migrant’s child and being a migrant oneself. The analysis of Weronika’s case is also an attempt to show the relationship between the individual experience of the narrator and the mechanisms of collective influence. Thus, the text treats the analyzed life history as one of the biographical accounts reflecting the biographical and social processes assigned to a specific time frame. In this perspective, the text aims to reconstruct the complexity of these processes and to interpret the experienced social reality in an individual biography.